ASSESSMENT SYSTEMS BASED ON ARTIFICIAL INTELLIGENCE IN EDUCATION - Ibodullayeva Zubayda Sherzodovna (New modern researchers: modern proposals and solutions, 2025)
This article explores the application of artificial intelligence (AI) in educational assessment systems. AI-based assessment tools provide personalized feedback, automate grading, and analyze learner behavior to improve educational outcomes. The study discusses the benefits of efficiency, scalability, and objectivity, while also addressing concerns such as data privacy, algorithmic bias, and the need for teacher oversight. It offers a comprehensive overview of current AI technologies used in assessment and their implications for future educational practices.